Peran UMKM Mango Lova dalam Meningkatkan Perekonomian Mahasiswa Universitas Bina Sarana Informatika - Amalia Dwi Ramdhini; Desi Marlina; Ine Nova Ayu; Esa Putri Amalia; Siti Hanifatu Sya`adah (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the role of Micro, Small, and Medium Enterprises (UMKM) Mango Lova in enhancing the economic welfare of students at Universitas Bina Sarana Informatika. UMKM Mango Lova, which operates in the culinary sector, has become one of the primary options for students to meet their daily consumption needs while also serving as a source of income. The methodology used in this research is a qualitative approach, with data collected through interviews and surveys with students and the business owner. The results indicate that the presence of UMKM Mango Lova not only contributes to improving students' economies by providing job opportunities but also supports the sustainability of the local economy. Additionally, students involved in this UMKM gain valuable entrepreneurial experience, which can enhance their skills and competitiveness in the future. Overall, UMKM Mango Lova plays an important role in creating an economic ecosystem that supports student development and regional economic growth. This study is expected to provide insights for UMKM managers and educational institutions in developing strategies to support economic growth among students.